2021
DOI: 10.3390/biom11091339
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Acute Myelocytic Leukemia Cells to the Dienone Compound VLX1570 Is Associated with Inhibition of the Ubiquitin-Proteasome System

Abstract: Dienone compounds with a 1,5-diaryl-3-oxo-1,4-pentadienyl pharmacophore have been widely reported to show tumor cell selectivity. These compounds target the ubiquitin-proteasome system (UPS), known to be essential for the viability of tumor cells. The induction of oxidative stress, depletion of glutathione, and induction of high-molecular-weight (HMW) complexes have also been reported. We here examined the response of acute myeloid leukemia (AML) cells to the dienone compound VLX1570. AML cells have relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Proteins such as membrane proteins, cell cycle regulators, transcription factors, tumor suppressors and oncogenes, are ubiquitinated and play roles in different cellular activities (4,5,7). Ubiquitin-proteasome pathway is reported to be essential in leukemia (30)(31)(32) and ubiquitin ligases participated in the development and resistance of different leukemia (33)(34)(35)(36). Therefore, we had a thought that WWP2 play roles in apoptosis of ALL by regulate substrate protein as ubiquitin ligase by ubiquitin-proteasome pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins such as membrane proteins, cell cycle regulators, transcription factors, tumor suppressors and oncogenes, are ubiquitinated and play roles in different cellular activities (4,5,7). Ubiquitin-proteasome pathway is reported to be essential in leukemia (30)(31)(32) and ubiquitin ligases participated in the development and resistance of different leukemia (33)(34)(35)(36). Therefore, we had a thought that WWP2 play roles in apoptosis of ALL by regulate substrate protein as ubiquitin ligase by ubiquitin-proteasome pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins such as membrane proteins, cell cycle regulators, transcription factors, tumor suppressors and oncogenes, are ubiquitinated and play roles in different cellular activities [4,5,7]. Ubiquitin-proteasome pathway is reported to be essential in leukemia [28][29][30] and ubiquitin ligases participated in the development and resistance of different leukemia [31][32][33][34]. And it was reported that E3 ubiquitin ligases also play other roles in leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of oxidative stress, depletion of glutathione, and induction of high-molecular-weight (HMW) complexes by these compounds have also been reported. Selvaraju and colleagues [ 3 ] reported that sensitivity of acute myelocytic leukemia (AML) cells to the dienone compound VLX1570 is associated with UPS inhibition. The authors first examined the response of AML cells to VLX1570.…”
mentioning
confidence: 99%